DNA Barcode of symbiotic chironomids: Findings in the genus Symbiocladius (Diptera: Chironomidae) - Velásquez-Rodríguez, Karen; Lin, Xiao-Long; Sánchez-Vendizú, Pamela; Loayza-Muro, Raúl; Huamantinco, Ana; Prat, Narcís (Zootaxa, 2023)
Chironomidae of symbiotic habits have been recorded in different parts of the world, among commensals and parasites. There are different genera reported at the moment, however questions such as the origin of commensal or parasitic life, which occurred first or what are their benefits remain debatable. In order to contribute with information to elucidate the above mentioned issues, the present study reports the finding of immature stages of Symbiocladius (Acletus) wygodzinskyi Roback, 1965 in the Churup stream located in the Andes Cordillera (Peru), living on nymphs of Leptophlebiidae (Ephemeroptera). We present a morphological description of immature stages of this species and for the first time the sequence of COX1 gene S. (A.) wygodzinskyi. The genetic result also supports differences between the morphospecies of Symbiocladius (Symbiocladius) rhithrogenae Zavřel, 1924 and S. (A.) wygodzinskyi in 23%.